Society as process Essays in Social Sciences method - Nieuwenhuijze, C.A.O. Van (Mouton & Co., 1962)
The present essays are given up to a cluster of problems that nowadays interfere with the work of social scientists in various fields of the social sciences. They are, however, problems few people are inclined to pay attention to in a more than cursory manner. This in its turn is why they may in the long run affect the normal progress of the social sciences in an adverse manner. Never fully in the limelight, they are almost unchecked whilst exerting their influence for better but probably for worse. They would thus require to be dragged into the open, for every one to look at their real scope and nature. Now as it happens, chances are that, once someone would try to do this, he may get the impression that all of a sudden he has gone off the right track. The issues one is bound to face appear, at first sight, far away from the usual haunts of social scientists. Yet upon a second glance one realizes that never the less they are entirely relevant, and even basic, to the subject matters social scientists will occupy themselves with in the daily practice of their work.
Keywords: Society